A case study in enhancing analytical preparedness through education technology. (2015) - Valentine, Scott Victor; Kooperberg, Ronaye; Bateman, Tim
This paper critically analyses an actual case involving the design of an online discussion board intended to foster analytical learning preparedness. The goal of the study was to consider how instructional design theory could be applied to foster a more effective design. The conclusion highlights how user training, enhanced instructor engagement, strategic design of discussion questions, devolving responsibility to learners and adopting clear evaluation strategies can significantly improve the efficacy of the technology.